FabLab London: case study of a creative entrepreneur - Gregson, Andrew (Henry Stewart Talks, 2016)
Ande Gregson is a restless serial entrepreneur and active networker with an approach that is far removed from textbook advice. He does not prepare formal business plans and relies greatly on his feel ‘for the direction in which things are moving’. FabLab is ‘a space with machines to make things’ in the heart of the City of London. In these premises paying subscribers rent machines to make prototypes for anything from half an hour to a few days at a time. In this interview Ande describes what FabLab is, what it does, why and how he set it up and the plans for its future.